Good manufacturing practices and microbial contamination sources in orange fleshed sweet potato puree processing plant in Kenya - Derick, N.M.; Muzhingi, T.; George, O.A. (Hindawi Limited, 2018)
Limited information exists on the status of hygiene and probable sources of microbial contamination in Orange Fleshed Sweet Potato (OFSP) puree processing. The current study is aimed at determining the level of compliance to Good Manufacturing Practices (GMPs), hygiene, and microbial quality in OFSP puree processing plant in Kenya. Intensive observation and interviews using a structured GMPs checklist, environmental sampling, and microbial analysis by standard microbiological methods were used in data collection. The results indicated low level of compliance to GMPs with an overall compliance score of 58%. Microbial counts on food equipment surfaces, installations, and personnel hands and in packaged OFSP puree were above the recommended microbial safety and quality legal limits. Steaming significantly (P<0.05) reduced microbial load in OFSP cooked roots but the counts significantly (P<0.05) increased in the puree due to postprocessing contamination. Total counts, yeasts and molds, Enterobacteriaceae, total coliforms, and E. coli and S. aureus counts in OFSP puree were 8.0, 4.0, 6.6, 5.8, 4.8, and 5.9 log<sub(10)> cfu/g, respectively. In conclusion, equipment surfaces, personnel hands, and processing water were major sources of contamination in OFSP puree processing and handling. Plant hygiene inspection, environmental monitoring, and food safety trainings are recommended to improve hygiene, microbial quality, and safety of OFSP puree.